Potential Molecular Targets in the Setting of Chemoradiation for Esophageal Malignancies. (22nd December 2020) - Jabbour, Salma K; Williams, Terence M; Sayan, Mutlay; Miller, Eric D; Ajani, Jaffer A; Chang, Andrew C; Coleman, Norman; El-Rifai, Wael; Haddock, Michael; Ilson, David; Jamorabo, Daniel; Kunos, Charles; et al.
Abstract: Although the development of effective combined chemoradiation regimens for esophageal cancers has resulted in statistically significant survival benefits, the majority of patients treated with curative intent develop locoregional and/or distant relapse. Further improvements in disease control and survival will require the development of individualized therapy based on the knowledge of host and tumor genomics and potentially harnessing the host immune system. Although there are a number of gene targets that are amplified and proteins that are overexpressed in esophageal cancers, attempts to target several of these have not proven successful in unselected patients. Herein, we review our current state of knowledge regarding the molecular pathways implicated in esophageal carcinoma, and the available agents for targeting these pathways that may rationally be combined with standard chemoradiation, with the hope that this commentary will guide future efforts of novel combinations of therapy.